PENGARUH STOCK SELECTION ABILITY DAN MARKET TIMING ABILITY TERHADAP KINERJA REKSA DANA SYARIAH SAHAM MENGGUNAKAN MODEL CONDITIONAL DAN UNCONDITIONAL PADA PERIODE 2009 – 2015 - Mustofa, Fani Sabila; Kusumawardhani, Amie (Faculty of Economics and Business Diponegoro University, 2016)
This study aims to evaluate the performance of Islamic mutual fund shares to examine the relationship between stock selection ability and market timing ability on the performance of Islamic mutual fund shares. The study is also to discover the model of performance measurement that is better adapted to the measurement of the performance of Islamic mutual fund shares in Indonesia. Data used in this study is the monthly data Net Asset Value (NAV), SBIS and JII of 8 Islamic mutual fund shares that were sampled, as well as changes in exchange rates and inflation as conditional control the study period 2009-2015. From the analysis it is found the best model which is the model of Treynor- Mazuy Conditional.The results shows the positive effect of stock selection ability on performance of the islamic mutual fund shares. However the study was not able to show the positive relationship between market timing ability and stock selection ability. The study also shows that majority of the performance of islamic mutual fund shares are better than their benchmarck, except PNM Syariah Equity.